Effects of Initial Water Temperature and Soaking Duration on the Germination of Canarium (Canarium indicum) Seeds - Aqshan Shadikin Nurdin; Ramli Hadun; Bagus Dimas Setiawan; Laswi Irmayanti; Reyna Ashari (Jurnal Sylva Lestari, 2022)
Canarium (Canarium indicum) seeds have mechanical dormancy, i.e., seeds have a hard outer seed coat, which causes inhibition of germination. Mechanical dormancy can be broken by mechanical and chemical scarification. One way of chemical scarification is water soaking. This study aimed to analyze the initial effect of temperature of the soaking water and duration of soaking on the germination of canarium seeds. The research design used was a two-factor experiment in a completely randomized design. The first factor is the different initial water temperature and the second factor is soaking duration. The initial water temperature consists of 60°C, 70°C, 80°C, 90°C, and 100°C, while the soaking duration consists of 0 h, 24 h, 48 h, and 72 h. The results showed that the initial water temperature had a very significant effect on germination percentage, peak value, mean daily germination, and germination value. The soaking duration did not significantly affect germination percentage, mean daily germination, and germination value, but it significantly affected the peak value. The interaction of initial water temperature and soaking duration significantly affected the germination percentage, mean daily germination, peak value, and germination value. The initial water temperature and soaking duration affected the germination of canarium seeds. Keywords: Canarium indicum, dormancy, germination, initial temperature, soaking duration